PENGARUH PENDEKATAN VISUAL THINKING TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA - Erdawati Nurdin; Hayatun Nufus; Hasanuddin Hasanuddin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to see the effect of visual thinking approach on improving students' mathematical connection ability. This is a quasi-experimental research with nonequivalent control group design. The sample is students on class VIII in Madrasah Tsanawiyah which is chosen by using purposive sampling technique. The research instruments used are a test of mathematical connection ability and an observation sheet. The results of the observations showed an increase in the activity of students and teachers in each meeting in the classroom that obtained learning by using visual thinking approach. The data of increased connection ability is not normally distributed, so the data analysis is done using U non-parametric test of Mann Whitney. From the data analysis, it can be concluded that there is no significant effect of learning by using visual thinking approach to students’ mathematical connection ability improvement.